Your answer is xy-1<span><span>
</span></span><span>=<span><span><span><span>4<span>x2</span></span><span>y2</span></span>−<span><span>4x</span>y/</span></span><span><span>4x</span>y
</span></span></span><span>=<span><span><span><span>4x</span>y</span>−4/</span>4
</span></span><span>=<span><span>xy</span>−<span>1
</span></span></span>Hope this helps!
Answer:
LtoG
7.4072
7.608
7.67
7.7
Step-by-step explanation:
Answer:
multiply both sides by 3x + 7
Step-by-step explanation:
this will eliminate the fraction in the equation and therefore make it easier to isolate x
hope this helps :)
We know that
surface area of the square pyramid=area of the base+4*[area of lateral triangle]
area of the base=b²----> area of square
b=6 ft
area of square=6*6---> 36 ft²
area of lateral triangle=b*h/2
b=6 ft
h=9 ft
area of lateral triangle=6*9/2---> 27 ft²
surface area of the square pyramid=36+4*27----> 144 ft²
the answer is
144 ft²